EFEKTIVITAS BIOLARVASIDA EKSTRAK DAUN KEMANGI (Ocimum basilicum) TERHADAP LARVA Aedes aegypti - Anastasia Christella Christella; Robby Makimian; Rita Dewi (Bahasa Indonesia, 2020)
Introduction: Indonesia as a tropical country is vulnerable to mosquito-borne diseases like dengue fever, chikungunya, and zika by Aedes aegypti mosquito. Various efforts have been made to eradicate mosquitoes, one of which is by fogging. But this method only eradicates adult mosquitoes and its smoke can also have a bad impact for human health. Therefore, a variety of herbal plants began to be used as biolarvacide, including basil plants (Ocimum basilicum). Methods: This is an experimental research by comparing the lethal effect between concentration and time. In this experiment there were 10 larvas used for each concentration, which were 0,4%, 0,7%, 1,0%, 1,5%, and 2,0%. The lethal effect arising in larval groups is observed every 1 hour in the first 6 hours, and subsequently every 3 hours until 24 hours after exposure. Results: With one way ANOVA test, the result is p=0,012 (p<0,05) this shows that there is a significance difference between the different concentrations and the lethal effect of A.aegypti larvae. With Friedman test, the result is p=0,000 (p<0,05), this shows that there is a significance difference between the different time of exposure of the extract and the lethal effect of A.aegypti larvae. Conclusion: Leaves extract of O.basilicum has lethal effect as biolarvacide against A.aegypti larvae. The higher concentration and the longer time of exposure to O.basilicum extract, increases the lethal effect of A.aegypti larvae.